Environmental Consequences of the Peace: The Great War, Dammed Lakes, and Hydraulic History in the Eastern Alps. (6th May 2015) - Landry, Marc
Abstract: This article examines hydropower development in early twentieth-century Bavaria to suggest the importance of peace settlements in the environmental history of war. At the turn of the twentieth century, the Alpine lake Walchensee became the center of plans to transform the Alpine lake into a reservoir. At this time, engineers across the Alps recommended converting high-altitude lakes into reservoirs. The new infrastructure would deepen the hydroelectric transition in the Alps, enabling the substitution of hydro for coal and expanding water power's role in the electricity supply. Despite the Bavarian state's determination to take advantage of the Walchensee's energy storage capabilities, societal and political opposition brought the project to a standstill on the eve of the First World War. The pressure of total war subsequently convinced Bavarians to move forward; however, crises accompanying the peace settlement of Versailles—above all Germany's loss of coal reserves due to territorial changes—ensured that Bavaria finally broke ground on the facility in the postwar period. The Walchensee reservoir did fulfill some of its energy promises, but only at the price of dramatic environmental change. The new landscape of energy storage disrupted ecological and human communities alike. Only in the post–World War II period did Bavarians consider revising aspects of this environmental legacy of Versailles.